Path to Prosperity - Wolfowitz,Paul (2016)
Paul Wolfowitz, President of the World Bank, discussed Singapore's remarkable progress along the road from poverty to prosperity which has also been discovered by many other countries in East Asia and around the world. He spoke of how each country must find its own path for people to pursue the same dreams of the chance to go to school, the security of a good job, and the ability to provide a better future for their children. Throughout the world, and importantly in the developing world, there is a growing recognition that the path to prosperity must be built on a solid foundation of good governance. Rich countries that have a vital responsibility in the fight against corruption and the need to take action against bribe givers who often come from their countries and to help the developing country partners recover stolen assets. He concluded by saying that the Bank’s mission is to help pave the way for the poor by giving them opportunity to work, so that they can take control of their own destiny.